The Effect of Feeding Time in Toddlers on Stunting in Indonesia: Systematic Review - Verawati Agustien; Mariyani Mariyani (Global Health Science Group, 2023)
Stunting is a disorder of growth and development experienced by children as a long-term manifestation of malnutrition and recurrent infections. Previous research has shown that one of the problems in infant feeding is the cessation of breastfeeding and insufficient breastfeeding. The purpose of this study was to conduct a systematic study on the effects of premature breastfeeding on the incidence of stunting in Indonesia. This study was conducted by systematic review. Research data is sought from several indexing including: PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. By using the search keywords